2021
DOI: 10.1021/acsaem.1c03057
|View full text |Cite
|
Sign up to set email alerts
|

Graphitic Carbon Nitride Codoped with Sulfur and Yttrium for Efficient Visible-Light Photocatalytic Performance

Abstract: The correlation of electronic band structure and photocatalytic performance of graphitic carbon nitride (g-C3N4) provides important perspectives for understanding the catalytic mechanism and developing efficient catalysts. Herein, sulfur and yttrium codoped graphite carbon nitride (Y/S–CN) was prepared by a facile calcination process of melamine, 2-thiobarbituric acid, and yttrium nitrate hexahydrate at elevated temperatures. The hydrogen evolution rate of the optimal 0.01Y/S–CN photocatalyst reached 19.2 μmol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…These exhibit excellent photocatalytic efficiency during the process of organic pollutant degradation (dye and antibiotic). 13 15 g-C 3 N 4 is a low-cost photocatalyst capable of generating H 2 and H 2 O 2 from water, and CDs exhibit high catalytic activity during H 2 O 2 decomposition. Liu et al demonstrated that the combination of g-C 3 N 4 and CDs exhibited a synergism on the processes of H 2 O 2 decomposition and • OH production in the absence of light irradiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These exhibit excellent photocatalytic efficiency during the process of organic pollutant degradation (dye and antibiotic). 13 15 g-C 3 N 4 is a low-cost photocatalyst capable of generating H 2 and H 2 O 2 from water, and CDs exhibit high catalytic activity during H 2 O 2 decomposition. Liu et al demonstrated that the combination of g-C 3 N 4 and CDs exhibited a synergism on the processes of H 2 O 2 decomposition and • OH production in the absence of light irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the mineralization efficiency of organic pollutants and reduce operating costs, EBI is usually applied with addition of some oxidants like H 2 O 2 , ozone, persulfate, and the metal catalysts such as Fe 2+ and TiO 2 . Composites formed by graphitic carbon nitride (g-C 3 N 4 )/carbon nanodots (CDs) doped with metals have been extensively studied. These exhibit excellent photocatalytic efficiency during the process of organic pollutant degradation (dye and antibiotic). g-C 3 N 4 is a low-cost photocatalyst capable of generating H 2 and H 2 O 2 from water, and CDs exhibit high catalytic activity during H 2 O 2 decomposition. Liu et al demonstrated that the combination of g-C 3 N 4 and CDs exhibited a synergism on the processes of H 2 O 2 decomposition and • OH production in the absence of light irradiation .…”
Section: Introductionmentioning
confidence: 99%
“…From the spectra, the atomic contents of the S element were calculated to be 0.75 wt% and 0.86 wt% in SCN and PSCN samples, respectively. The binding energy of S 2p in PSCN at around 168.5 eV was assigned to S—C bonds formed by replacing the N atoms with the S atoms [47] . Furthermore, for SCN and PSCN, similar patterns of C 1 s and N 1 s spectra without significant binding energy shifts were observed.…”
Section: Resultsmentioning
confidence: 99%
“…Melon, an uncondensed form of g-C 3 N 4 , attracted attention recently. [27][28][29] It has been used as a precursor for the synthesis of graphitic carbon nitride (g-C 3 N 4 ) since its discovery by Berzelius in the 1830s. [30] It also comprises tri-striazine subunits linked through a planar tertiary amino group with a layered structure.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the NH 2 groups on the surface could provide reactive centers for the preparation of composites through covalent tailoring or weak intermolecular interactions with other functional molecules. [34,35] Frequently, attempts are made to overcome the shortcomings of metal-free carbon nitride photocatalysts by substitution (i.e., "doping") with nonmetals, [28,29,36,37] by copolymerization, [38,39] or with hybrid heterostructures or nanocomposites. [40,41] Nanocomposites with conductive materials are an intriguing option to improve the charge separation efficiency of semiconductors.…”
Section: Introductionmentioning
confidence: 99%